Acid pH Increases SARS-CoV-2 Infection and the Risk of Death by COVID-19 - Jimenez, Leandro; Campos Codo, Ana; Sampaio, Vanderson de Souza; Oliveira, Antonio E. R.; Ferreira, Lucas Kaoru Kobo; Davanzo, Gustavo Gastão; Brito Monteiro, Lauar de; Victor Virgilio-da-Silva, João; Borba, Mayla Gabriela Silva; Fabiano de Souza, Gabriela; Zini, Nathalia; Andrade Gandolfi, Flora de; et al. (Frontiers in Medicine, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can infect a broad range of human tissues by using the host receptor angiotensin-converting enzyme 2 (ACE2). Individuals with comorbidities associated with severe COVID-19 display higher levels of ACE2 in the lungs compared to those without comorbidities, and conditions such as cell stress, elevated glucose levels and hypoxia may also increase the expression of ACE2. Here we showed that patients with Barrett’s esophagus (BE) have a higher expression of ACE2 in BE tissues compared to normal squamous esophagus, and that the lower pH associated with BE may drive this increase in expression. Human primary monocytes cultured in reduced pH displayed increased ACE2 expression and viral load upon SARS-CoV-2 infection. We also showed in two independent cohorts of COVID-19 patients that previous use of proton pump inhibitors is associated with 2- to 3-fold higher risk of death compared to those not using the drugs. Our work suggests that pH has a great influence on SARS-CoV-2 Infection and COVID-19 severity.